Interactive Multimedia Based on Project Based Learning Model Using Articulate Storyline 3 Material for Fifth-Grade Elementary School - I Wayan Darma; I Gede Margunayasa; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2024)
This study addressed the need for more interactive media in the learning process, which has led to low student performance. The goal was to develop Project-Based Learning (PjBL) model-based Interactive Multimedia using Articulate Storyline 3 for Water Cycle material in Grade V Elementary School that is feasible, practical, and effective in enhancing student learning outcomes. The research followed the ADDIE model: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. Subjects were Grade V students, and the focus was on their learning outcomes for the Water Cycle material. Data collection involved quantitative observation and tests using rating scale sheets and multiple-choice tests. Data analysis included average score analysis for feasibility and practicality and a correlated t-test for effectiveness. Results indicated that: (1) the average feasibility score of the media was 4.76, and the material test score was 4.63, both rated very high; (2) the average practicality test score was 4.70 by teachers and 4.97 by students, both rated very good; and (3) the significance value in the one-sample t-test was 0.000, showing the PjBL model-based Interactive Multimedia with Articulate Storyline 3 effectively improved student learning outcomes for the Water Cycle material in Grade V. Thus, the research concludes that Interactive Multimedia is feasible, practical, and effective in enhancing student learning outcomes for the Water Cycle material in Grade V Elementary School.